Enhancement of nucleus pulposus repair by glycoengineered adipose-derived mesenchymal cells. (April 2022) - Ying, Liwei; Liang, Chengzhen; Zhang, Yujie; Wang, Jingkai; Wang, Chenggui; Xia, Kaishun; Shi, Kesi; Yu, Chao; Yang, Biao; Xu, Haibin; Zhang, Yuang; Shu, Jiawei; et al.
Abstract: Adipose-derived mesenchymal stem cells (ADSCs) are promising candidates for repairing degenerated intervertebral discs through multiple means, including: i. Secretion of bioactive factors to regulate inflammation and, ii. The potential to differentiate into nucleus pulposus (NP)-like cells, which can integrate into host tissues. However, the differentiation ability of ADSCs to NP-like cells is limited, which emphasizes on the need for alternative approaches to regulate cell differentiations. Given that cell functions are influenced by interactions between the extracellular matrix (ECM) and cells, we hypothesize that cell surface modification promotes ADSCs adhesion and differentiation towards NP-like cells. In this study, cell surfaces of ADSCs were functionalized with unnatural sialic acid via metabolic glycoengineering. Subsequently, adhesion abilities of modified cells to three main ECM (laminin, collagen and fibronectin) were compared. The adhesion assay revealed that glycoengineered ADSCs had the highest affinity for collagen, compared to laminin and fibronectin. Moreover, cultures with collagen coated plates enhanced the differentiation of glycoengineered ADSCs to NP-like cells. Metabolic glycoengineering prolonged ADSCs viability. The glycoengineered ADSCs increased the height and elasticity of intervertebral discs, as well as the water content and ECM volumes of nucleus pulposus. In conclusion, metabolic glycoengineering of cell surfaces has a significant role in modulating cell biological functions and promoting NP tissue repair.